2022
DOI: 10.1620/tjem.2022.j059
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genes and Associated Drugs in Advanced Clear Cell Renal Cell Carcinoma by Bioinformatic Methods

Abstract: Identification of novel genes and associated drugs in advanced clear cell renal cell carcinoma by bioinformatic methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Interestingly, our study revealed TOP2A as the key hub gene in the PBMCs of individuals who received the second dose of COVID-19 mRNA vaccine, indicating a potential similarity between COVID-19 infection (live virus) and vaccination (spike protein of the virus) to some extent. Previous research on TOP2A primarily focused on kidney cancer, where its upregulation was associated with prognosis and considered a potential target for mRNA vaccine development [38][39][40][41][42][43][44][45][46]. TOP2A was upregulated in kidney cancer, could predict the prognosis, and might be a tumor target to guide mRNA vaccine development [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our study revealed TOP2A as the key hub gene in the PBMCs of individuals who received the second dose of COVID-19 mRNA vaccine, indicating a potential similarity between COVID-19 infection (live virus) and vaccination (spike protein of the virus) to some extent. Previous research on TOP2A primarily focused on kidney cancer, where its upregulation was associated with prognosis and considered a potential target for mRNA vaccine development [38][39][40][41][42][43][44][45][46]. TOP2A was upregulated in kidney cancer, could predict the prognosis, and might be a tumor target to guide mRNA vaccine development [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…(vii) Amonafide, a naphthalimide, was initially tested to treat acute myeloid leukemia and breast cancer. By intercalating DNA and blocking the binding of topoisomerases, amonafide promotes apoptotic cell death [96] and was effective against HepG2 and Huh7 cells [97]. The synthetic aminoacridine derivative (viii) amsacrine has a mechanism of action similar to amonafide and showed potential effects in treating malignant lymphoma and acute myeloid leukemia [98].…”
Section: Discussionmentioning
confidence: 99%
“…2,10 Network pharmacology (NP) and molecular docking (MD) offer a comprehensive grasp of network theory and system biology, which contributes to the account for the mechanism of medications. 15 Previous studies using NP and MD have revealed the possible targets and mechanisms of HCQ treatment in autoimmune diseases. 16,17 The current study retrieved possible targets of LN, IgAN, and HCQ by data mining.…”
Section: Introductionmentioning
confidence: 99%